An eight‐case 1q21 region series: novel aberrations and clinical variability with new features. Issue 6 (18th February 2019) - Ceylan, A. C.; Sahin, I.; Erdem, H. B.; Kayhan, G.; Simsek‐Kiper, P. O.; Utine, G. E.; Percin, F.; Boduroglu, K.; Alikasifoglu, M.
Abstract: Background: Rearrangement of the 1q21 region of chromosome 1 manifests as multiple phenotypes, including microcephaly, intellectual disability, dysmorphic facial features, eye abnormalities, cardiac defects, genitourinary anomalies, autism spectrum disorder, psychiatric conditions and seizures. Herein, we describe eight patients with 1q21 deletion and duplication syndromes, and novel deletions and findings. Methods: Chromosomal microarray analysis was performed to identify the existence of copy number variation. Quantitative polymerase chain reaction was applied using specific primers for the control and 1q21 region of chromosome 1. Mutational analysis was performed in case 5 using direct genomic sequencing for exons 1–6 in RBM8A . Results: Copy number variation analysis identified seven deletions and one duplication of the 1q21 region in the eight patients. In addition, four variations were de novo, and two deletions are reported here for the first time. One of the cases (case 7) presents moderate intellectual disability and dysmorphic facial findings, whereas chromosomal microarray analysis showed that case 7 had an 889‐kb deletion in the 1q21 proximal region (GPR89A, PDZK1, CD160, POLR3C and NBPF12). Conclusion: Although the deletion in case 5 did not include the thrombocytopenia‐absent radius syndrome critical region or the RBM8A gene, he had pectoral muscle hypoplasia, radius and humerus hypoplasia and short curved ribs, which are indicative of a potential thrombocytopenia‐absent radius region modifier. The findings in case 7 suggest that the proximal part of the 1q21 microdeletion syndrome region might be very important for the onset of clinical manifestations. Some novel findings were observed in the presented cases, such as radius and humerus hypoplasia and brain stem hypoplasia. The presented findings expand the spectrum of 1q21 aberrations and provide evidence of genotype–phenotype correlations for this region.